Evaluation of Temperature Prediction Methods for Mass Concrete Members - Riding, Kyle A.; Poole, Jonathan L.; Schindler, Anton K.; Juenger, Maria C. G.; Folliard, Kevin J. (My University, 2006)
Over the years, many different simplified prediction methods have been developed to predict the temperature development within mass concrete members. This paper compares calculated temperature values from three commonly-used concrete temperature prediction methods to actual temperatures in eight different concrete bridge members measured during construction. A simple temperature calculation method, the graphical method of ACI 207.2R, and a numerical heat transfer method (the Schmidt Method) were used to predict peak temperatures. The Schmidt Method performed the best when semi-adiabatic calorimetry results were used in the analysis. Suggestions are made on ways to improve the best technique, which was the Schmidt Method.
Keywords: Heat; Mass concrete; Temperature